Fundus Autofluorescence in the Abca4(−/−) Mouse Model of Stargardt Disease—Correlation With Accumulation of A2E, Retinal Function, and Histology - Charbel Issa, Peter (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To investigate fundus autofluorescence (AF) characteristics in the Abca4(−/−) mouse, an animal model for AMD and Stargardt disease, and to correlate findings with functional, structural, and biochemical assessments. METHODS. Blue (488 nm) and near-infrared (790 nm) fundus AF images were quantitatively and qualitatively analyzed in pigmented Abca4(−/−) mice and wild type (WT) controls in vivo. Functional, structural, and biochemical assessments included electroretinography (ERG), light and electron microscopic analysis, and A2E quantification. All assessments were performed across age groups. RESULTS. In Abca4(−/−) mice, lipofuscin-related 488 nm AF increased early in life with a ceiling effect after 6 months. This increase was first paralleled by an accumulation of typical lipofuscin granules in the retinal pigment epithelium (RPE). Later, lipofuscin and melanin granules decreased in number, whereas melanolipofuscin granules increased. This increase in melanolipofuscin granules paralleled an increase in melanin-related 790 nm AF. Old Abca4(−/−) mice revealed a flecked fundus AF pattern at both excitation wavelengths. The amount of A2E, a major lipofuscin component, increased 10- to 12-fold in 6- to 9-month-old Abca4(−/−) mice compared with controls, while 488 nm AF intensity only increased 2-fold. Despite pronounced lipofuscin accumulation in the RPE of Abca4(−/−) mice, ERG and histology showed a slow age-related thinning of the photoreceptor layer similar to WT controls up to 12 months. CONCLUSIONS. Fundus AF can be used to monitor lipofuscin accumulation and melanin-related changes in vivo in mouse models of retinal disease. High RPE lipofuscin may not adversely affect retinal structure or function over prolonged time intervals, and melanin-related changes (melanolipofuscin formation) may occur before the decline in retinal function.